2021
DOI: 10.1139/cjpp-2019-0456
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory properties of alpha-lipoic acid protect against valproic acid–induced liver injury

Abstract: Valproic acid (VPA) is one of the most used anti-epileptic drugs inspite of its many adverse effects as anemia, leucopenia, thrombocytopenia, and liver toxicity. The hepatoprotective effect of alpha-lipoic acid (ALA) was confirmed. Aim of the study: The aim of this study was to detect the protective effect of ALA against the adverse effects of VPA. Materials& Methods: Thirty white albino Wistar male rats were divided into 4 groups. Group (1) was the control group; Group (2) included rats that received ALA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Oxidative stress is also responsible for TNF‐α and JNK activation associated inflammation and necrosis 56,57 . SV was shown to mediate hepatotoxicity via TNF‐α, and NF‐κB activation and increased IL‐6 and COX‐2 expressions in experimental animals 26,58–60 . Consistent with the above studies, this study also reports increased pro‐inflammatory marker expression upon SV administration.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Oxidative stress is also responsible for TNF‐α and JNK activation associated inflammation and necrosis 56,57 . SV was shown to mediate hepatotoxicity via TNF‐α, and NF‐κB activation and increased IL‐6 and COX‐2 expressions in experimental animals 26,58–60 . Consistent with the above studies, this study also reports increased pro‐inflammatory marker expression upon SV administration.…”
Section: Discussionsupporting
confidence: 88%
“…IL-6, interleukin-6; NF-κB, nuclear factor kappa B; JNK, c-Jun N-terminal Kinase; IKKB, Inhibitor of nuclear factor kappa-B kinase subunit beta; SIL-silymarin and JNK activation associated inflammation and necrosis 56,57. SV was shown to mediate hepatotoxicity via TNF-α, and NF-κB activation and increased IL-6 and COX-2 expressions in experimental animals 26,[58][59][60]. Consistent with the above studies, this study also reports increased pro-inflammatory marker expression upon SV administration.…”
mentioning
confidence: 99%
“…In the model of mouse inflammatory bowel diseases (IBD), ALA was found to reduce the plasma levels of LPS and systemic inflammation in mice with colitis [ 54 ]. In human health-related studies, ALA was found to reduce the TNF-α and IL-6 levels in many organs and tissues through its anti-inflammatory properties [ 49 , 55 ]. Another study indicated a beneficial effect of ALA administration by reducing the serum and liver levels of TNF-α and IL-1β in rabbits fed oxidized nutrition oils [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Alpha-lipoic acid also protects against valproic acid-induced liver injury. 26 The combination of ALA, acetyl-L-carnitine (ALCAR), and coenzyme CoQ10 may provide an effective strategy in preventing anti-TB DILI. 27 ALA and silymarin treatment ameliorate thioacetamide (TAA)-induced oxidative damage,alterations in the liver function tests and liver histopathology in male albino rats.…”
Section: Introductionmentioning
confidence: 99%